Diffuse gliomas in patients aged 55 years or over: A suggestion for IDH mutation testing. Issue 1 (22nd November 2019) - Barresi, Valeria; Eccher, Albino; Simbolo, Michele; Cappellini, Rekha; Ricciardi, Giuseppe K.; Calabria, Francesca; Cancedda, Marco; Mazzarotto, Renzo; Bonetti, Bruno; Pinna, Giampietro; Sala, Francesco; Ghimenton, Claudio; et al.
Abstract : Diffuse gliomas are defined on the isocitrate dehydrogenase (IDH) gene ( IDH ) mutational mutational status. The most frequent IDH mutation is IDH1 R132H, which is detectable by immunohistochemistry; other IDH mutations are rare (10%). IDH mutant gliomas have better prognosis. Further, IDH wild‐type low‐grade (II/III) gliomas have clinical behaviors similar to those of glioblastoma (GBM) and it was suggested that they are submitted to similar post‐surgical treatment. The incidence of IDH mutant gliomas (2%) and that of GBMs with non‐canonical IDH mutations (< 1%) are very low in patients ≥ 55 years. For this reason, it was suggested that immunohistochemistry against IDH1 R132H is sufficient to classify GBM as IDH wild‐type in this age group. However, no indication was provided for IDH mutational testing in low‐grade diffuse gliomas. To address this issue, 273 diffuse gliomas were tested for IDH1 R132H immunohistochemistry. 2/4 diffuse astrocytomas (DAs), 4/9 anaplastic astrocytomas (AAs), 2/256 GBMs, and 4/4 oligodendrogliomas had positive staining. No other IDH mutations were found in immuno‐negative low‐grade cases by DNA sequencing. To validate our findings, we considered 311 diffuse gliomas in patients ≥ 55 years in The Cancer Genome Atlas database. Fifty‐five out of 311 gliomas had IDH R132H mutations (9/16 DAs; 8/48 AAs; 3/211 GBMs; 35/36 oligodendrogliomas), one DA, and one oligodendroglioma had other IDH mutations. IDH mutant gliomas had significantly higher frequency of O‐6‐methylguanine‐DNA methyltransferase promoter methylation ( P = 0.0008) and longer overall survival ( P < 0.0001). In conclusion, low‐grade gliomas are a minor part of gliomas (117/584) in patients ≥ 55 years, albeit they represent most IDH mutant gliomas in this age group (64/69 cases). IDH non‐canonical mutations can be found in immunonegative low‐grade gliomas (2/54). In view of its significance for prognosis and therapeutic management, our results suggest that IDH mutational status is assessed in all diffuse gliomas in patients ≥ 55 years by immunohistochemistry, followed by IDH sequencing in low‐grade immunonegative cases.